Integration of Al-Ghazali and Ibn Khaldun's Developmental Psychology in The Reconstruction of Contemporary Islamic Religious Education: A Spiritual-Pragmatic Pedagogical Model - Adona, Putri; Sospita, Devi; Niimmasubhani, Niimmasubhani; Charles, Charles (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
Contemporary Islamic Religious Education (PAI) is often hindered by a theoretical dichotomy that separates profound spiritual values (Al-Ghazali's psycho-spiritual focus on Qalb purification) from the necessities of social pragmatism and vocational skills (Ibn Khaldun's sociology of education). This gap compromises PAI's ultimate goal of forming holistic individuals (Insan Kamil). This research addresses this critical inadequacy by formulating an explicitly integrated model of developmental psychology for PAI. Employing a philosophical comparative methodology, robustly supported by a systematic review and synthesis of evidence from books and articles, the study analyzes the necessary convergence between Al-Ghazali’s framework and Ibn Khaldun’s pedagogy, including ‘Umran and Tadarruj (gradual learning). The central finding is the Progressive Ethical Habitus Model. This model resolves the classical philosophical conflict: it utilizes Ibn Khaldun’s structured, phased methodology as the essential practical framework for internalizing the spiritual and ethical content of Al-Ghazali. This integration ensures that moral values transition from theoretical understanding into a permanent, functional disposition (Habitus), successfully reconstructing PAI to produce graduates who are both spiritually robust and socially adaptive to complex global challenges and modern moral crises.